Copper-cobalt double-metal composite MOF material, preparation method thereof and application of copper-cobalt double-metal composite MOF material in hydrogen evolution by electrolyzing water
Through the preparation of copper-cobalt bimetallic composite MOF materials, the problems of high cost of precious metal catalysts and low activity of single metal MOF are solved, and high efficiency electrolysis of hydrogen and stability are achieved, providing the application direction of high-performance electrocatalysts.
Patent Information
- Application Number
- CN202411277031.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-17
AI Technical Summary
The existing electrolytic water hydrogen production catalysts mainly rely on precious metal Pt, which is costly and limited in resources, limiting large-scale applications, and the single-metal MOF materials are not very active in electrocatalysis.
Using copper-cobalt bimetallic composite MOF material, the molar ratio and calcination temperature of copper and cobalt are optimized to form a catalyst with high specific surface area and conductivity.
It realizes efficient electrolysis of hydrogen, improves the number of active sites and conductivity, reduces resistance, accelerates electron transfer, and has good stability and electrochemical properties.
Smart Images

Figure CN119144998A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and in particular relates to a copper-cobalt bimetallic composite MOF material, a preparation method thereof, and an application thereof in hydrogen evolution by electrolysis of water. Background Art
[0002] At present, non-renewable energy such as coal, oil and natural gas are used in large quantities. However, due to limitations of technology and other reasons, the utilization rate is low and the environment is polluted. Therefore, people realize that it is of great significance to develop new energy to replace traditional non-renewable energy. Solar energy is widely used, easy to collect and has huge reserves. The disadvantages are dispersion and high cost. Wind energy has large reserves and wide distribution, but its energy density is low, unstable, and restricted by geographical location. Hydrogen has good combustion performance and an energy density of up to 142.5kJ / kg. It is considered to be the main development direction of new energy in the future. The technology of hydrogen production by electrolysis of water is clean and efficient. Its oxidation product is water, which is very friendly to the environment and has high purity. It is currently considered to be the most promising hydrogen production technology.
[0003] Metal-organic frameworks (MOFs) use metal ions as the connection center and organic ligands as bridges, usually connected in the form of hydrogen bonding, van der Waals forces and coordination bonds. Compared with traditional materials, MOF materials have more advantages in some aspects, such as large specific surface area, adjustable and orderly pore structure, and the ability to expose more active sites. Many studies are based on MOF materials and use them as precursors to prepare different MOF derivatives. Their derivatives often retain the original structural characteristics. For example, when constructing porous carbon derivatives, they can effectively prevent the agglomeration of metal nano-ions and the collapse of the structure during the calcination process, and they have a large specific surface area and a unique 3D structure. The porous carbon materials obtained by high-temperature calcination greatly improve the conductivity of the material. The unique 3D structure is conducive to the adsorption of water and the desorption of hydrogen adsorption intermediates, which is conducive to the electrocatalytic process. However, the most advanced catalyst for hydrogen evolution by electrolysis of water is still Pt-based precious metal catalysts. However, due to the objective problems such as the high cost of precious metal catalysts and insufficient resource reserves, large-scale practical applications are severely restricted. Therefore, the preparation of MOF materials for use in water electrolysis to generate hydrogen has great application prospects. Summary of the invention
[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0006] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a copper-cobalt bimetallic composite MOF material.
[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising:
[0008] The copper source is dissolved in DMF, and triethylenediamine and terephthalic acid are added, stirred evenly and then subjected to hydrothermal reaction. After the reaction is completed, the mixture is cooled, filtered and dried to obtain Cu-MOF.
[0009] Cu-MOF is dissolved in methanol, and a surfactant, 2-methylimidazole, and a cobalt source are added, and the mixture is stirred, centrifuged, washed, and dried to obtain a copper-cobalt bimetallic composite MOF material.
[0010] As a preferred embodiment of the method for preparing the copper-cobalt bimetallic composite MOF material of the present invention, the copper source comprises Cu(NO 3 ) 2 , CuCl 2 、CuSO 4 One or more of .
[0011] As a preferred embodiment of the method for preparing the copper-cobalt bimetallic composite MOF material of the present invention, the cobalt source comprises Co(NO 3 ) 2 、CoCl 2 One or more of .
[0012] As a preferred embodiment of the method for preparing the copper-cobalt bimetallic composite MOF material of the present invention, the surfactant comprises one or more of polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate.
[0013] As a preferred scheme of the preparation method of the copper-cobalt bimetallic composite MOF material of the present invention, wherein: the hydrothermal reaction, wherein the reaction temperature is 110-130° C., and the reaction time is 35-40 hours.
[0014] As a preferred embodiment of the method for preparing the copper-cobalt bimetallic composite MOF material of the present invention, the mass ratio of the copper source, triethylenediamine and terephthalic acid is 3-4:2-3:3-4.
[0015] As a preferred scheme of the preparation method of the copper-cobalt bimetallic composite MOF material of the present invention, the mass ratio of the Cu-MOF, surfactant and 2-methylimidazole is 1:1-3:6-10.
[0016] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a copper-cobalt bimetallic composite MOF material. The molar ratio of copper to cobalt in the composite MOF material is 1:8-12.
[0017] The purpose of the present invention is to overcome the deficiencies in the prior art and provide an application of a copper-cobalt bimetallic composite MOF material in hydrogen evolution by electrolysis of water. The copper-cobalt bimetallic composite MOF material is ground and calcined to serve as a catalyst for hydrogen evolution by electrolysis of water.
[0018] As a preferred solution for the application of the copper-cobalt bimetallic composite MOF material of the present invention, the calcination temperature is 700°C to 900°C, the heating rate is 4 to 6°C / min, and the calcination time is 1.5 to 2.5h.
[0019] Beneficial effects of the present invention:
[0020] The copper-cobalt bimetallic composite MOF material prepared by the present invention can realize efficient water electrolysis and hydrogen evolution as a catalyst, increase the number of active sites, have a larger specific surface area, can expose more active sites, and the conductivity of the material after calcination is further improved. The synergistic effect between Cu and Co accelerates the material's adsorption efficiency of water and the desorption rate of adsorbed hydrogen intermediates, reduces the material's resistance, and accelerates the electron transfer rate. At a current density of 10 mA / cm 2 The hydrogen evolution overpotential of 96 mV was achieved. It has good stability, and its electrochemical performance is significantly improved compared with the material obtained by calcining the single metal MOF precursor under the same conditions, which provides some ideas for the future development of efficient composite MOF materials for electrocatalysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0022] Figure 1 The XRD patterns of the materials prepared in the examples and comparative examples of the present invention are shown in FIG. Figure 1 (a) XRD patterns of Cu-MOF, ZIF-67, CuCo composite MOF and CuCo-700; Figure 1 (b) XRD patterns of ZIF-67, Cu-MOF and CuCo composite MOF materials calcined at 700 °C.
[0023] Figure 2This is the curve obtained after impedance testing of the copper-cobalt bimetallic composite MOF and CuCo-700 materials prepared in the test example of the present invention.
[0024] Figure 3 TEM images of ZIF-67 (a), Cu-MOF (b), and CuCo composite MOF (c).
[0025] Figure 4 LSV test curves of hydrogen evolution of ZIF-67-700, Cu-MOF-700 and CuCo-700.
[0026] Figure 5 This is a test curve of electrochemical hydrogen evolution stability of the CuCo-700 material prepared in Example 1.
[0027] Figure 6 This is the XRD pattern of the catalyst CuCo-700 prepared in Example 1.
[0028] Figure 7 This is a curve chart obtained by conducting hydrogen evolution LSV test on the catalysts prepared in Examples 1, 2 and 3. DETAILED DESCRIPTION
[0029] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0030] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0031] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0032] Unless otherwise specified, the raw materials used in the present invention are all commercially available in the art.
[0033] The material prepared in the embodiment of the present invention was subjected to hydrogen evolution LSV test as follows:
[0034] Preparation method of working electrode: Before use, the carbon cloth is immersed in an acetone solution for 20 minutes of ultrasonic treatment, and then immersed in an anhydrous ethanol solution. After cleaning, it is placed in an oven at 60°C for drying, and then loaded with powdered catalyst. Weigh 5 mg of CuCo@C and other series catalyst powders, dissolve in 1 mL of anhydrous ethanol, and add 20 μL of Nafion binder, and perform ultrasonic treatment at room temperature. After ultrasonic treatment for 30 minutes, drip it on the carbon cloth drop by drop, and dry it at room temperature to obtain the working electrode to be tested.
[0035] Electrochemical tests were performed at room temperature using an electrochemical workstation model PARSTAT4000 (USA). The electrolyte was an alkaline electrolyte, i.e., 1M KOH, and before the test, a nitrogen atmosphere was passed through the electrolyte for 30 minutes to ensure that the test would not be affected by the presence of oxygen. A standard three-electrode system was selected, in which the working electrode was a carbon cloth coated with a catalyst, the reference electrode was a Hg / HgO electrode, and a graphite rod was used as the counter electrode. Finally, all test potentials were converted to standard potentials relative to the reversible hydrogen electrode (RHE) using the formula E(vs.RHE)=E(vs.Hg / HgO)+0.0591pH+0.098, and plotted.
[0036] Electrochemical hydrogen evolution stability test: Under a fixed potential, record the change in current caused by the continuous extension of time, draw the IT curve, calculate the current density at the end of the time, and make the difference with the current density at the beginning to judge the stability of the catalyst.
[0037] Example 1
[0038] Weigh 0.37 g of Cu(NO 3 ) 2 ·3H 2 O was added to 75 mL DMF with mechanical stirring, and 0.24 g triethylenediamine and 0.34 g terephthalic acid were added, and the mixture was stirred for 1 h and then transferred to a reactor; the mixture was hydrothermally reacted at 120° C. for 36 h, and after the reaction was completed, the reactor was cooled to room temperature and filtered, and then dried at 60° C. for 12 h to obtain a Cu-MOF material;
[0039] 0.1 g Cu-MOF was weighed and dissolved in 50 mL methanol, and 0.2 g polyvinyl pyrrolidone, 0.8 g 2-methylimidazole, 0.291 g Co(NO 3 ) 2 6H 2 O, stirred for 24 hours, centrifuged, washed, and dried for 12 hours to obtain a CuCo composite MOF material with a molar ratio of cobalt to copper of 1:10.
[0040] 0.5 g of CuCo composite MOF material was weighed and calcined at 700° C. for 2 h in a nitrogen atmosphere at a heating rate of 2° C. / min to obtain the catalyst CuCo-700.
[0041] Comparative Example 1
[0042] Weigh 0.8 g of 2-methylimidazole, 0.291 g of Co(NO 3 ) 2 6H 2 O was dissolved in 50 mL of methanol solution, stirred at room temperature for 24 h, and then centrifuged, washed, and dried for 12 h to obtain ZIF-67.
[0043] 0.5 g ZIF-67 was weighed and calcined at 700° C. for 2 h in a nitrogen atmosphere at a heating rate of 2° C. / min to obtain a catalyst ZIF-67-700.
[0044] Comparative Example 2
[0045] Weigh 0.37 g of Cu(NO 3 ) 2 ·3H 2 O was added into 75 mL DMF solution with mechanical stirring, and 0.24 g triethylenediamine and 0.34 g terephthalic acid were added and stirred for 1 h before being transferred into a reactor. The reaction was hydrothermally reacted at 120 ° C for 36 h. After the reaction was completed, the reactor was cooled to room temperature and filtered, and dried at 60 ° C for 12 h to obtain Cu-MOF material.
[0046] 0.5 g of Cu-MOF material was weighed and calcined at 700° C. for 2 h in a nitrogen atmosphere at a heating rate of 2° C. / min to obtain the catalyst Cu-MOF-700.
[0047] Figure 1 (a) is the XRD spectrum of Cu-MOF, ZIF-67, CuCo composite MOF and CuCo-700. The composite MOF has the characteristic diffraction peaks of Cu-MOF and ZIF-67. At the calcination temperature of 700℃, the characteristic peaks of CuCo-700 correspond to Co and Cu, respectively. Figure 1 (b) is the XRD spectrum of ZIF-67, Cu-MOF and CuCo composite MOF after calcination at 700°C. It can be seen that the characteristic peak of Cu-MOF after calcination also exists in CuCo-700, but the diffraction peak is shifted. It may be due to the introduction of ZIF-67 that a certain synergistic effect is formed between the two, thus promoting the material to have better electrocatalytic performance.
[0048] Figure 2This is the curve obtained after the impedance test of CuCo composite MOF and CuCo-700 materials. From the EIS impedance graph, it can be clearly observed that the calcined material has a smaller resistance and a faster electron transfer rate.
[0049] Figure 3 TEM images of ZIF-67 (a), Cu-MOF (b), and CuCo composite MOF (c). It can be seen that the block-shaped CuMOF grows relatively evenly on the surface of ZIF-67, and the CuCo composite MOF has a good structure. The design of the material relies on the advantage of the structure-adjustable growth of MOFs materials.
[0050] Figure 4 The curves obtained by LSV test of hydrogen evolution of ZIF-67-700, Cu-MOF-700 and CuCo-700. It can be seen that the performance of hydrogen evolution in electrolysis of water by CuCo composite MOF after calcination is significantly better than that of Cu-MOF-700 and ZIF-67-700 obtained by calcining single metal MOF as precursor.
[0051] Figure 5 This is a curve diagram of the electrochemical hydrogen evolution stability test of the catalyst CuCo-700 prepared in this example. It can be seen that after a long-term test of 20 hours, the catalyst can still maintain 83% of the initial current density, indicating that the material has good stability.
[0052] Figure 6 This is the XRD pattern of the catalyst CuCo-700 prepared in this example. The characteristic peaks correspond to Cu element (PDF#85-1326) and Co element (PDF#89-7093).
[0053] Example 2
[0054] The difference between this embodiment and embodiment 1 is that the calcination temperature of the CuCo composite MOF material is adjusted to 800° C., and the rest of the preparation process is the same as that of embodiment 1, to obtain the catalyst CuCo-800.
[0055] Example 3
[0056] The difference between this embodiment and embodiment 1 is that the calcination temperature of the CuCo composite MOF material is adjusted to 900° C., and the rest of the preparation process is the same as that of embodiment 1, to obtain the catalyst CuCo-900.
[0057] Figure 7 The curves obtained by the LSV test of hydrogen evolution of the catalysts prepared in Examples 1, 2, and 3 show that CuCo-700 has a current density of 10 mA / cm -2It has the lowest overpotential when , which is significantly better than CuCo-800 and CuCo-900.
[0058] Comparative Example 3
[0059] The difference between this comparative example and Example 1 is that the calcination temperature of the CuCo composite MOF material is adjusted to 500° C., and the rest of the preparation process is the same as that of Example 1, to obtain the catalyst CuCo-500.
[0060] Comparative Example 4
[0061] The difference between this comparative example and Example 1 is that the calcination temperature of the CuCo composite MOF material is adjusted to 600° C., and the rest of the preparation process is the same as that of Example 1, to obtain the catalyst CuCo-600.
[0062] The hydrogen evolution performance of the materials prepared in the above-mentioned embodiments and comparative examples was tested, and the comparison results with those of Example 1 are shown in Table 1.
[0063] Table 1
[0064] Example 1 Example 2 Example 3 Comparative Example 3 Comparative Example 4 Hydrogen evolution overpotential (mV) 96 137.6 148.3 252.6 168.8
[0065] As can be seen from the above table, adjusting the calcination temperature has a significant effect on the performance of the copper-cobalt bimetallic composite MOF material. This is because calcination causes the disintegration or rearrangement of the crystal structure of the MOF material. Too high or too low a temperature will cause the metal organic framework in the MOF to undergo a phase change or reorganization, resulting in the loss of the original catalytic active sites or a reduction in performance. It will also cause copper and cobalt to form oxides or other inactive substances or metal particles to aggregate, reducing the efficiency of the hydrogen evolution reaction. When the copper-cobalt bimetallic composite MOF material is calcined in the range of 700°C to 900°C, the material has a lower overpotential of 96mV, 137.6mV, and 148.3mV, respectively. When the calcination temperature is not in this range, the hydrogen evolution performance of the material obtained is poor. In summary, the preferred calcination temperature of the present invention is 700°C.
[0066] Example 5
[0067] The difference between this embodiment and embodiment 1 is that the molar ratio of cobalt to copper is adjusted to 1:8, and the rest of the preparation process is the same as that of embodiment 1 to obtain a catalyst.
[0068] Example 6
[0069] The difference between this embodiment and embodiment 1 is that the molar ratio of cobalt to copper is adjusted to 1:12, and the rest of the preparation process is the same as that of embodiment 1 to obtain a catalyst.
[0070] Comparative Example 5
[0071] The difference between this comparative example and Example 1 is that the molar ratio of cobalt to copper is adjusted to 1:20, and the rest of the preparation process is the same as that of Example 1 to obtain a catalyst.
[0072] Comparative Example 6
[0073] The difference between this comparative example and Example 1 is that the molar ratio of cobalt to copper is adjusted to 1:5, and the rest of the preparation process is the same as that of Example 1 to obtain a catalyst.
[0074] The hydrogen evolution performance of the materials obtained in the above embodiments and comparative examples was tested, and the comparison results with those of embodiment 1 are shown in Table 2.
[0075] Table 2
[0076] Example 1 Example 4 Example 5 Comparative Example 4 Comparative Example 5 Hydrogen evolution overpotential (mV) 96 134 126.4 302.6 284.2
[0077] As can be seen from the above table, adjusting the molar ratio of cobalt and copper has a significant effect on the performance of copper-cobalt bimetallic composite MOF materials. The molar ratio of copper and cobalt in MOF affects the transfer of electrons and catalytic activity in the catalytic reaction. Improper molar ratio of copper and cobalt may lead to unsatisfactory electronic effect of the catalyst, thereby reducing the catalytic performance. The molar ratio of copper and cobalt will also affect the framework structure of the material, the coordination environment of the metal center, and the distribution of active sites in the catalyst. Certain molar ratios may cause structural instability of MOF or reduce the synergistic effect of the metal center. Synergistic effect is usually the key to the catalytic hydrogen evolution reaction of metal complexes, so unreasonable molar ratios lead to decreased catalytic efficiency. When the molar ratio of cobalt to copper is 1:10, the material has the best hydrogen evolution performance. When the molar ratio is in the range of 1 / 8 to 1 / 10, the hydrogen evolution performance of the material is relatively excellent. After exceeding this range, the hydrogen evolution overpotential of the material is too high and basically does not have hydrogen evolution performance. In summary, the preferred molar ratio of cobalt and copper in the present invention is 1:10.
[0078] Comparative Example 7
[0079] The difference between this comparative example and Example 1 is that the precursor is adjusted to MIL-101(Fe), and the rest of the preparation process is the same as that of Example 1 to obtain a catalyst. Specifically:
[0080] Weigh 0.824 g of terephthalic acid crystals, add them to 30 mL of N,N-dimethylformamide (DMF) solution, stir for 40 min, and then weigh 1.350 g of FeCl 3 6H 2 O was added to the above mixed solution and stirred for 20 min to make the solution completely mixed, then transferred to a 50 mL stainless steel polytetrafluoroethylene reactor and crystallized in a 90 °C oven for 20 h. After the reactor was cooled to room temperature, it was centrifuged and dried at 60 °C for 12 h.
[0081] Post-treatment: Weigh 0.1g of the dried sample and add it to 50mL of DMF solution, stir in a constant temperature water bath at 80℃ for 12h to remove the unreacted terephthalic acid crystals in the pores and on the surface of MIL-101(Fe), centrifuge and dry at 60℃ for 12h; then add the dried sample to 50mL of anhydrous ethanol, stir in a constant temperature water bath at 60℃ for 12h to remove the DMF remaining on the surface and in the pores, centrifuge and dry at 60℃ for 12h, finally put the dried sample into a vacuum drying oven and dry at 150℃ for 12h to obtain the MIL-101(Fe) sample.
[0082] The hydrogen evolution performance test of the material prepared in the above comparative example was carried out, and the comparison results with those of Example 1 are shown in Table 3.
[0083] Table 3
[0084] Example 1 Comparative Example 7 Hydrogen evolution overpotential (mV) 96 123
[0085] It can be seen from the table that when different bimetallic composite MOFs are selected as precursors, the resulting material properties have large deviations.
[0086] In summary, the present invention synthesized a bimetallic composite MOFs material at room temperature, and prepared a high-performance water electrolysis hydrogen evolution catalyst by calcination, aiming to solve the problem of high cost and low natural abundance of Pt / C noble metal catalysts. At the same time, the derivatives prepared from the precursors of single metal MOFs materials have low catalytic activity. The bimetallic composite MOFs material prepared by the present invention has high electrocatalytic activity after calcination, and the synergistic effect between the two metals accelerates the hydrolysis rate of the material and the desorption efficiency of adsorbed hydrogen, and has a long cycle life.
[0087] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a copper-cobalt bimetallic composite MOF material, Features: include, The copper source is dissolved in DMF, and triethylenediamine and terephthalic acid are added, stirred evenly and then subjected to hydrothermal reaction. After the reaction is completed, the mixture is cooled, filtered and dried to obtain Cu-MOF. Cu-MOF is dissolved in methanol, and a surfactant, 2-methylimidazole, and a cobalt source are added, and the mixture is stirred, centrifuged, washed, and dried to obtain a copper-cobalt bimetallic composite MOF material.
2. The method for preparing the copper-cobalt bimetallic composite MOF material according to claim 1, Features: The copper source includes Cu(NO 3 ) 2 , CuCl 2 ,CuSO 4 One or more of .
3. The method for preparing the copper-cobalt bimetallic composite MOF material according to claim 1, Features: The cobalt source includes Co(NO 3 ) 2 、CoCl 2 One or more of .
4. The method for preparing the copper-cobalt bimetallic composite MOF material according to claim 1, Features: The surfactant includes one or more of polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate.
5. The method for preparing the copper-cobalt bimetallic composite MOF material according to claim 1, Features: The hydrothermal reaction has a reaction temperature of 110 to 130° C. and a reaction time of 35 to 40 hours.
6. The method for preparing the copper-cobalt bimetallic composite MOF material according to claim 1, Features: The mass ratio of the copper source, triethylenediamine and terephthalic acid is 3-4:2-3:3-4.
7. The method for preparing the copper-cobalt bimetallic composite MOF material according to claim 1, Features: The mass ratio of the Cu-MOF, the surfactant and the 2-methylimidazole is 1:1-3:6-10.
8. A copper-cobalt bimetallic composite MOF material prepared by the preparation method according to any one of claims 1 to 7, Features: The molar ratio of copper to cobalt in the composite MOF material is 1:8-12.
9. Application of the copper-cobalt bimetallic composite MOF material as claimed in claim 8 in hydrogen evolution by electrolysis of water, Features: The copper-cobalt bimetallic composite MOF material is ground and calcined to serve as a catalyst for hydrogen evolution in water electrolysis.
10. Use of the copper-cobalt bimetallic composite MOF material according to claim 8 in hydrogen evolution by electrolysis of water, Features: The calcination temperature is 700° C. to 900° C., the heating rate is 4 to 6° C. / min, and the calcination time is 1.5 to 2.5 hours.
